2021
DOI: 10.15294/biosaintifika.v13i2.30718
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Phyllanthus niruri, Euphorbia hirta, and Loranthus sp. as a Source of Antioxidant Agents

Abstract: Meniran (Phyllanthus niruri), patikan kebo (Euphorbia hirta), and benalu (Loranthus sp.) have often been used by people as medicinal plants. This research aimed to measure the levels of flavonoids, phenolics, and ascorbic acid compounds, as well as the Free Radical Scavenging (FRS) activity of ethyl acetate extract from the mixture of P. niruri, E. hirta, and Loranthus sp. The FRS activity was measured with the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The level of compounds was measured by using the spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
1
3
0
1
Order By: Relevance
“…and S. ferruginea have very strong antioxidant capacity, equivalent to the strength of ascorbic acid. These results are in accordance with the report of Kristiani & Kasmiyati (2021) reported that the antioxidant ability of the ethanolic extract of Lorathus sp. strong with an IC50 value of 97.2 g/ml.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…and S. ferruginea have very strong antioxidant capacity, equivalent to the strength of ascorbic acid. These results are in accordance with the report of Kristiani & Kasmiyati (2021) reported that the antioxidant ability of the ethanolic extract of Lorathus sp. strong with an IC50 value of 97.2 g/ml.…”
Section: Resultssupporting
confidence: 94%
“…Several studies have shown that the reducing ability of Loranthus extracts exhibits dose-dependent properties, such as in Loranthus begins's L. (Oboh et al, 2016). Scurrula ferruginea (Marvibaigi et al, 2014), the combination of Loranthus with Phyllanthus niruri and Euphorbia hirta (Kristiani & Kasmiyati, 2021). The strength of antioxidant capacity of a material can be determine based on the IC50 value (Molyneux, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…This was supported by a previous study that the combination of medicinal plants had no synergistic properties in bacterial growth inhibition [16]. Kristen and Kasmiyati, 2021 [22] stated, that the combination of Phyllanthus niruri, Euphorbia hirta, and Loranthus sp. leaf extracts at a ratio = 0:0:1 obtained the strongest antioxidant activity.…”
Section: Discussionmentioning
confidence: 57%
“…The filtrate was then concentrated by using a rotary evaporator at 400C to obtain a thick extract of Meniran and Kenikir leaves. The ethanolic extract of Meniran and Kenikir leaves used for antibacterial activity test was at 50% concentration [21,22].…”
Section: Extraction Of Meniran and Kenikir Leavesmentioning
confidence: 99%
“…Nilai tersebut jauh lebih tinggi dibanding ekstrak lain yang ada pada kisaran 170 -740 µg ekivalen bioaktif/g ekstrak. Hasil tersebut didukung oleh penelitian Kristiani & Kasmiyati (2021) yang menunjukkan bahwa senyawa fenol lebih berkorelasi dengan kemampuan antioksidan dibandingkan flavonoid atau asam askorbat.…”
Section: Bunclassified